Representation of the Muslim Brotherhood in contemporary Egyptian newspapers - Youssef, Sara Abouelmaaty Mogahed (AUC Knowledge Fountain, 2014)
This is a qualitative exploratory study that examines the representation of the Muslim Brotherhood (MB) in contemporary Egyptian newspapers. It aims to reveal the linguistic features that contribute to the construction of a positive or negative image of the MB in the data. The study uses the Discourse Historical Approach (DHA) in analyzing its data. This approach mainly looks at representation strategies, in particular, nomination, predication and argumentation strategies, which are primarily manifested through lexical choices. The data for the study consist of 18 articles from two Egyptian newspapers, Al-Hurryya wa Al-Adala "Freedom and Justice" and Al-Wattan "The Homeland". The former is the official newspaper of Al-Hurryya wa Al-Adala party, the political arm of the MB. The latter is an independent newspaper that is generally known to take an opposing stand towards the MB. With respect to the main nomination strategies, the analysis shows that in the data from Al-Wattan newspaper, members of the MB have been very frequently referred to by words and phrases that carry explicit or implicit negative evaluations, e.g. by referring to their complete obedience to MB leadership, MB secrecy, and accusations of violence and backwardness. On the other hand, Al-Hurryya wa Al-Adala newspaper refers to MB using words and phrases that very frequently carry explicit or implicit positive evaluations, e.g. by describing them as the legitimate ruling power and as a group that is deeply rooted in the Egyptian society. Regarding the predication strategies, some of the most salient qualities attributed to the MB in Al-Wattan newspaper are failure and incapability, being a threat to Egypt, secrecy, and backwardness. In Al-Hurryya wa Al-Adala, a number of predications that carry positive evaluations have been used to describe the MB, e.g. piety, success, having a glorious past and being loved by the people. Finally, as for the argumentation strategies, in Al-Wattan, a number of claims are made against the MB, e.g. responsibility for polarization, using religion, ikhwanizing the state and privatizing the revolution for the interest of the group. Al-Hurryya wa Al-Adala, on the other hand, used some counter arguments based on a set of topoi and fallacies, e.g. by claiming that there is a conspiracy against the MB and by blaming Mubarak's regime and the opposition for the MB economic failure and political mistakes. By selecting these strategies, among other ones, both newspapers focus on arguments that best serve their purposes. For example, by referring to MB violence, Al-Wattan attempts to revive what people remember of the past of the MB and some other Islamic groups, hence portraying an image that scares people off the MB. Also, highlighting the failure of president Mursi and the MB government to meet people’s essential daily needs is a claim that targets the majority of Egyptians, educated and none educated, since all Egyptians are affected by this failure. On the other hand, Al-Hurryya wa Al-Adala combined topoi of conspiracy and being under attack from the media as a scapegoat strategy to blame the mistakes of the government on a second party. This is also used as an answer to the claim of failure. If the country is destroyed and corruption is everywhere then it is not the responsibility of the MB government, rather it is the responsibility of the old regime and the opposition. Such scapegoat strategies are applied throughout the data and illustrate a typical pattern of argumentation. The findings of this study could be used to help advanced Arabic language students be discerning readers and could provide a model for teaching that focuses on critical reading of media texts.